Surgical management of atrial-esophageal fistula as a complication of atrial fibrillation ablation. Issue 1 (26th January 2022) - Duda, Amber; Beers, Kevin; Mitiek, Mohi
Abstract: Atrial-esophageal fistula (AEF) is a rare, but life-threatening complication of ablative treatments for atrial fibrillation. Although the incidence of this complication is low, the mortality is very high. There are many surgical approaches to this disease but we offer a novel technique to reduce the number of incisions used and provides central cannulation. It also allows for repair of both the esophagus and atrium and buttresses these repairs, which have both been shown to decrease morbidity and mortality. The technique has been successful in our three patients and can be considered as an approach to surgical management of AEF.